Tetraconatan phylogeny with special focus on Malacostraca and Branchiopoda: highlighting the strength of taxon-specific matrices in phylogenomics - Schwentner, Martin; Richter, Stefan; Rogers, D. Christopher; Giribet, Gonzalo (Proceedings of the Royal Society B : Biological Sciences, 2018)
Understanding the evolution of Tetraconata or Pancrustacea—the clade that includes crustaceans and insects—requires a well-resolved hypothesis regarding the relationships within and among its constituent taxa. Here, we assembled a taxon-rich phylogenomic dataset focusing on crustacean lineages based solely on genomes and new-generation Illumina-generated transcriptomes, including 89 representatives of Tetraconata. This constitutes, to our knowledge, the first phylogenomic study specifically addressing internal relationships of Malacostraca (with 26 species included) and Branchiopoda (36 species). Seven matrices comprising 81–684 orthogroups and 17 690–242 530 amino acid positions were assembled and analysed under five different analytical approaches. To maximize gene occupancy and to improve resolution, taxon-specific matrices were designed for Malacostraca and Branchiopoda. Key tetraconatan taxa (i.e. Oligostraca, Multicrustacea, Branchiopoda, Malacostraca, Thecostraca, Copepoda and Hexapoda) were monophyletic and well supported. Within Branchiopoda, Phyllopoda, Diplostraca, Cladoceromorpha and Cladocera were monophyletic. Within Malacostraca, the clades Eumalacostraca, Decapoda and Reptantia were well supported. Recovery of Caridoida or Peracarida was highly dependent on the analysis for the complete matrix, but it was consistently monophyletic in the malacostracan-specific matrices. From such examples, we demonstrate that taxon-specific matrices and particular evolutionary models and analytical methods, namely CAT-GTR and Dayhoff recoding, outperform other approaches in resolving certain recalcitrant nodes in phylogenomic analyses.